PEMBIAYAAN SEKOLAH BERBASIS SASARAN: PERBANDINGAN BUKTI EMPIRIS DARI BELGIA (FLANDERS) DAN KOREA SELATAN - Listina, Listina; Heriyanto, Heriyanto; Sutrisno, Sutrisno (Jurnal Manajemen Pendidikan, 2026)
Education funding that allocates additional resources to schools with a concentration of vulnerable or low-achieving students is a common policy instrument in many countries. This article presents a systematic synthesis of two recent empirical studies evaluating the causal effects of such funding using a regression discontinuity design (RDD) approach: Badunenko et al.'s (2025) study on primary education in Flanders (Belgium) and Sohn et al.'s (2022) study on primary schools in South Korea under a centralized funding system. The theoretical review links the findings to the education production function, human capital theory, and the distinction between average and underachievement. The synthesis shows that policy design (target definition, beneficiary threshold, and use of funds) and outcome measures determine the interpretation of effectiveness: in Flanders, additional funding showed no significant impact on mathematics scores but reduced underachievement; in South Korea, an increase in funding per pupil of approximately 20 percent at the policy threshold was associated with a decrease in the proportion of below-average students in most subjects, except reading. Implications for research and policy are discussed narratively.